Banks and shadow banks: Competitors or complements? - Górnicka, Lucyna A. (Journal of Financial Intermediation, 2016)
Bank managers can buy risky assets through a regulated bank and through an off-balance sheet special purpose vehicle (SPV). The choice of the preferred entity depends on whether bank managers can lower the cost of SPV funding by guaranteeing SPV returns with bank proceeds. When there are no guarantees, using the SPV is more profitable for high levels of the minimum capital requirement, in which case the SPV crowds out the bank. Contrary, when bank managers guarantee SPV returns, the bank needs to operate for the SPV to take advantage of recourse to the bank’s balance sheet also when the capital requirement is high. The bank and the SPV intermediation become complements.